2018
DOI: 10.1038/s41467-018-03870-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional materials in functional three-dimensional architectures with applications in photodetection and imaging

Abstract: Efficient and highly functional three-dimensional systems that are ubiquitous in biology suggest that similar design architectures could be useful in electronic and optoelectronic technologies, extending their levels of functionality beyond those achievable with traditional, planar two-dimensional platforms. Complex three-dimensional structures inspired by origami, kirigami have promise as routes for two-dimensional to three-dimensional transformation, but current examples lack the necessary combination of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
117
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(120 citation statements)
references
References 41 publications
0
117
0
Order By: Relevance
“…Kirigami has been transitioning to the toolbox of modern materials design. [6][7][8] The cut patterns endow materials with unusual mechanical properties such as the 2Dto-3D transformation, 9,10 predictive deformation, 7,11 and extensibility enhancement with negligible impact on conductance of a material, 12 thereby promoting the quick development in stretchable electronics, 6 sensors, 13 wearable devices, 12,14 as well as in energy conversion and storage applications. 12,15 Kirigami-inspired metamaterials can programmatically switch their physical properties by changing the…”
Section: Introductionmentioning
confidence: 99%
“…Kirigami has been transitioning to the toolbox of modern materials design. [6][7][8] The cut patterns endow materials with unusual mechanical properties such as the 2Dto-3D transformation, 9,10 predictive deformation, 7,11 and extensibility enhancement with negligible impact on conductance of a material, 12 thereby promoting the quick development in stretchable electronics, 6 sensors, 13 wearable devices, 12,14 as well as in energy conversion and storage applications. 12,15 Kirigami-inspired metamaterials can programmatically switch their physical properties by changing the…”
Section: Introductionmentioning
confidence: 99%
“…The excellent conformality over 3D structures inherent to ALD will be demonstrated in a separate experiment on a 3D nano-trench structure. In literature, it has been shown that the integration of 2D TMDs on unconventional substrates with tailored geometry/functionality can offer vast opportunities for a variety of applications including gas sensor, photo detection and imaging, optoelectronics etc [35][36][37]. Furthermore, our PEALD based approach provides a route towards formation of seamless in-plane lateral heterostructures of 2D MoS 2 and WS 2 layers in a controlled way on technologically relevant SiO 2 /Si substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Releasing the prestrain then triggers the out-of-plane buckling of the 2D precursors, lifting them off from the substrate surface at the non-bonded weak interfaces, and thereby leading to the formation of 3D mesostructures with programmed configurations. Due to the high level of design flexibility, a variety of complex 3D geometries can be realized [32], including open filamentary frameworks [28,33,34], mesostructures with hybrid geometries of membranes and filaments [11,31], folded constructs (e.g. origami-inspired mesostructures) [27,30] and highly filling nested or entangled networks [29].…”
Section: Introductionmentioning
confidence: 99%